The Most Influential Factors of Consumers’ Buying Pattern at Organized and Unorganized Retail Stores with Special Reference to Kakinada City, Andhra Pradesh - Burlakanti, Kuberudu; Srinivas, Romala Vijaya (Indian Journal of Marketing, 2013)
Recent emergence of organized retailing and its huge customer attraction and retention marketing strategies, the adoption of technology and patronizing retailing shops and value-added services have created a market space for them in India. The existing unorganized retailers have also started to add more number of product mix/product lines to their existing selling assortments in order to create a feeling of "one time and comprehensive shopping" in the minds of the consumers, so that the consumers prefer their stores for the next purchase. The consumers’ tentative buying patterns become a "riddle" for the organized and unorganized retailers. The researchers selected this particular topic and tried to analyze the perceptual changes in the retail sector with reference to organized and unorganized retailers. By studying the present topic, the researchers are shedding light on the state of mind of the consumers, which would be beneficial for both the organized and unorganized retailers, as insights about consumer behavior would help them to realign their present marketing/selling strategies to retain the customers for their businesses.